Javanese Ettiquete in The Novel Dua Tanda Kurung by Handoko F Zainsam - Urbaningrum, Dea Harumi; Anggraini, Purwati (Jurnal KATA, 2019)
The study is aimed to describe the life values of Javanese people contained in the novel Dua Tanda Kurung by Handoko F Zainsam. The object of the research is the novel Dua Tanda Kurung by Handoko F Zainsam. The source of the data in research is the text of the novel Dua Tanda Kurung by Handoko F Zainsam. The data is obtained from sentences or dialogues, unit of story that leads to the ethics of Javanese people live’s. The procedure of the research is: (1) reading the novel Dua Tanda Kurung by Handoko F Zainsam, (2) creating data sources, (3) reading data sources, (4) rearranging data based on theory, (5) classifying data, (6) analysing data and interpreting the data. The data dicussion are translated and analyzed in the form of a description. The used instruments are researchers who are assisted by data collectors, books, and other supporting media. There are three life ethics of the Javanese people, namely: 1) the principle of harmony, 2) the principle of respect, and 3) the ethics of sosial harmony. The ethics of social harmony or the principle of harmony contains absolute prohibition on efforts to act only on the basis of one’s awareness and will. In social harmony ethics there are seven ethics, namely mikul duwur mendem jero, rumangsa melu handarbeni, nrima ing pandum, lega lila, pasrah, sumarah, and rikuh pawekuh.